Pengenalan Konsep Matematika Berbasis Seriasi Melalui Media Logo Pada Anak - Mahyuddin, Nenny; Mainofriwita, Mainofriwita (Universitas Negeri Medan, 2023)
This study is the implementation of the introduction of serialization based mathematical concepts through lego media to children as an introduction to mathematics learning for young children including classification, seriation, patterns, number concepts, measurements, geometry, and problem solving experiences. One of them is the introduction of mathematical concepts based on seriation through Lego media which is a very popular game in the world, especially for children. Mathematical concepts in children aged 2-4 years where children can classify and classify shapes, colors, and sizes. So to develop a mathematical introduction to children based on seriation can use lego games. This study uses qualitative research methods which are descriptive qualitative in nature. Research data presented in descriptive form is sourced from data that has been collected in the form of recordings, interviews, photos, documentation. The findings of the study are that the lego games that are performed on children become enthusiastic and obtain learning of mathematical concepts based on seriation. In this article, it is explained how the introduction of serialization-based mathematics using lego at the age of 2-4 years.